The un role in combating international terrorism: achievements and challenges (Revista de Investigaciones Universidad del Quindío, 2022)
Terrorism continues to be an urgent international problem, despite a slight decrease in terrorist activity after the military defeat of ISIS * in Syria and Iraq. This article attempts to examine the main areas of the UN counter-terrorist activities in the 2000s. The authors have revealed the importance of the Global Counter-Terrorism Strategy for intensifying the combat against global terrorism. The content of the institutional reform of the system of UN organizations that counter terrorism is described in detail. A special focus is on the tasks and functions of the Counter-Terrorism Committee, the Counter-Terrorism Center, and the UN Counter-Terrorism Office. Special attention is paid to the analysis of some unresolved problems in the activities of the UN as the center of the combat against terrorism in the world.
Keywords: Security Council; international terrorism; countering terrorism; Counter-Terrorism Committee.